KAUSALITAS EKONOMI MAKRO DAN GLOBAL TERHADAP PASAR MODAL INDONESIA - R Adisetiawan (Universitas Batanghari Jambi, 2018)
This study aims to determine causality macroeconomic variables and the influence of the Indonesian capital market during the period 2001-2017 by means of Granger causality test statistics and test of Multiple Linear Regression. The results of this study revealed that during the period 2001-2017 there is a relationship of causality between the money supply (M2) with the Indonesia Stock Exchange composite index, but there is no causal relationship between the BI rate, inflation, the price of crude oil, gold, exchange rate IDR/USD, Dow Jones and Nikkei 225 index on the Indonesia Stock Exchange composite index over the same period. The results of model testing research at 99% confidence level, obtained adjusted R-square values simultaneously at 98.4%, meaning that changes in the macro economy is able to provide a very significant variation in movement patterns of stock price index in Indonesia's capital market. This is also evidenced by the magnitude of the correlation values obtained in the model by 99.3%, meaning that there is a very close relationship between macroeconomic variables of the Indonesian capital market. However, the partial rate of inflation that occurred in Indonesia in the period 2001-2017 did not have a significant influence on the movement of stock market indices of Indonesia. Keywords: JCI, macroeconomic, globalization